Effect of interfacial Fe3O4 nanoparticles on the microstructure and mechanical properties of textured alumina densified by ultrafast high-temperature sintering - Behera, Rohit Pratyush (2024)
Alumina microplatelets coated with a small amount of Fe3O4 can be oriented via a rotating magnetic field to create texture. After ultrafast high-temperature sintering (UHS), Fe atoms are found at the grain boundaries and within the grains, influencing the mechanical properties. Here, we compare the microstructure and mechanical properties of textured alumina prepared with and without Fe3O4 and sintered using UHS or conventional sintering (CS). Microstructural analysis using electron backscattering diffraction (EBSD) indicates that Fe3O4 induces crystallographic defects in the ceramic after UHS. Nanoindentation measurements enlighten that the presence of Fe3O4 leads to plastic flow that increases the energy dissipation, reaching ~122 % at a maximum load of 1900 mN compared to pristine samples. Overall, due to the concentrated effects of Fe3O4 after UHS, the flexural strength and fracture toughness values are higher than the other two samples, reaching values of ~287 MPa and 7 MPa.m0.5, respectively. These results could be leveraged to produce stronger and tougher ceramics.